Debt Management Performance Assessment : Cabo Verde - World Bank (World Bank, Washington, DC, 2020)
This report assesses the debt management performance of the government of Cabo Verde by applying the 2015 World Bank debt management performance assessment (DeMPA) methodology. Overall, there have been positive developments in government debt management practices in Cabo Verde. Some of those developments are reflected in improved DeMPA scores, as in the case of the preparation of a medium-term debt management strategy (DMS), publication of debt management information, and documentation of procedures in the domestic market. In some other cases, improvements were not enough to change the scores, although relevant and acknowledged, such as the case of domestic borrowing. In a number of other dimensions, such as those related to debt recording and operational risk, challenges persist. Annex 1 brings a detailed update on the implementation of the debt management reform plan designed in 2013, showing good improvement in some areas, in particular the development of a DMS and debt management reporting, but less progress in operational risk management and data recording.